Processamento cerâmico e caracterização elétrica de cátodos Ca3-xCuxCo4O9-δ (0 ≤ x ≤ 0,2) obtidas pelo método de precursores poliméricos modificado - Lima, Chrystian Gregório Medeiros de (2016)
The search for alternative energy sources becomes very present in the current world scenario. A solution on the rise are fuel cells, which have the principle chemical energy conversion through fuel oxidation reaction into electrical energy. Among the major components of these cells are the electrodes (cathode and anode), the electrolyte, the interconnectors and sealants. This work aimed to develop cathode materials based on calcium cobaltite doped with copper oxide (CuO). To this end, powders of composition Ca3-xCuxCo4O9-δ (0 ≤ x ≤ 0.2) were obtained using the polymeric precursor method (Pechini method) modified with commercial gelatin. The as-prepared powders were calcined at 900 ° C for 1 h and characterized by X-ray diffractometry (XRD). The lattice parameters were determined by Rietveld refinement of the diffraction data. The powder morphology was analyzed by scanning electron microscopy (SEM). Porous films were deposited on both faces of ceria based electrolytes, via screen printing, and sintered at 950 °C for 2h. The electrochemical characterization of symmetric cell (cathode/electrolyte/cathode) was carried out by impedance spectroscopy between 600 and 800 ° C in air atmosphere. The results of X-ray diffraction indicated the obtainment of solid solutions Ca3-xCo4CuxO9 and up to 2 vol.% Co3O4 as a secondary phase. The values of lattice parameter were close to that reported in the ICSD standard, confirming the doping with Cu ions. The powders are comprised of microplates with an irregular shape measuring up to approximately 2 μm in diameter. The area specific resistance was optimized for the composition Ca2.99Co4Cu0.01O9, achieving 0.84 ohm.cm2 at 800 °C in air.